Molecular mechanism of lipid-induced cardiac insulin resistance and contractile dysfunction. (September 2018) - Liu, Yilin; Neumann, Dietbert; Glatz, Jan F.C.; Luiken, Joost J.F.P.
Abstract: Long-chain fatty acids are the main cardiac substrates from which ATP is generated continually to serve the high energy demand and sustain the normal function of the heart. Under healthy conditions, fatty acid β-oxidation produces 50–70% of the energy demands with the remainder largely accounted for by glucose. Chronically increased dietary lipid supply often leads to excess lipid accumulation in the heart, which is linked to a variety of maladaptive phenomena, such as insulin resistance, cardiac hypertrophy and contractile dysfunction. CD36, the predominant cardiac fatty acid transporter, has a key role in setting the heart on a road to contractile dysfunction upon the onset of chronic lipid oversupply by translocating to the cell surface and opening the cellular 'doors' for fatty acids. The sequence of events after the CD36-mediated myocellular lipid accumulation is less understood, but in general it has been accepted that the excessively imported lipids cause insulin resistance, which in turn leads to contractile dysfunction. There are several gaps of knowledge in this proposed order of events which this review aims to discuss. First, the molecular mechanisms underlying lipid-induced insulin resistance are not yet completely disclosed. Specifically, several mediators have been proposed, such as diacylglycerols, ceramides, peroxisome proliferator-activated receptors (PPAR), inflammatory kinases and reactive oxygen species (ROS), but their relative contributions to the onset of insulin resistance and their putatively synergistic actions are topics of controversy. Second, there are also pieces of evidence that lipids can induce contractile dysfunction independently of insulin resistance. Perhaps, a more integrative view is needed, in which several lipid-induced pathways operate synergistically or in parallel to induce contractile dysfunction. Unraveling of these processes is expected to be important in designing effective therapeutic strategies to protect the lipid-overloaded heart. Highlights: Dietary fat overconsumption leads to myocardial lipid accumulation and ultimately contractile dysfunction. Excessive myocellular fatty acid import is mediated by the membrane fatty acid transporter CD36 through its increased translocation from endosomes to the sarcolemma. The mechanism by which lipid accumulation results in contractile dysfunction includes lipid-induced cardiac insulin resistance but may also involve effects independent of insulin resistance. This review provides an overview of current mechanistic insight in lipid-induced cardiac contractile dysfunction.